Sistem Pengatur Akses Jalan Sempit Melalui Object Detection Menggunakan Algoritma YOLO - Putra, Iqshan Aditia; Ferdian, Rian (Universitas Andalas, 2026)
To enter the parking lot behind the Faculty of Engineering building, students, lecturers and other Unand residents usually have to pass through a small road that starts from the front of the KOPMA building to the parking portal of the Faculty of Engineering building. This small road is 3 meters wide and 110 meters long. Due to the small size of the road, it is quite difficult for two cars to pass through the road simultaneously. Therefore, a device is needed that can regulate the entry and exit of cars passing through the road so that there is no situation where two cars enter from two opposite sides. Thus making one of the two cars have to give in. The tool is implemented at two ends of the road entering the narrow road. The tool uses a Raspberry Pi 4 which functions as an object detection processing center to detect cars that want to enter the narrow road. After the car is detected, the device sends data wirelessly to the device at the other end of the road so that the vehicle stops waiting for the car to exit the road. Wireless communication uses LoRa SX1278 which can reach distances exceeding 100 meters. Because the device is installed outdoors, an alternative energy source is used, namely solar panels that can store energy by absorbing light from the sun